The Symbolic Type Revisited: Semiotics in Practice and the Reformation of the Israeli Commemorative Context. Issue 3 (2nd May 2016) - Kidron, Carol A.; Handelman, Don
Abstract : Revisiting Grathoff's theory of symbolic type (ST), we examine the personal evolution and commemorative work of Tsipi Kichler, a cultural entrepreneur and founder of an alternative Israeli Holocaust museum/geriatric center. As hybrid product of Israeli social cleavages, Kichler exteriorizes her paradoxical vision in the museum aiming to reform Holocaust‐related discourse and practice. Early biographical positioning and resultant contradictions become translated into resistant commemorative performance where serious humor deconstructs the binaries of life/death and past/present. We consider the implications of the ST's self‐referential closure to interaction, and the transformative potential of the alignment of cultural entrepreneurs' personal memory with collective memory.